Investigation of the grain structure of the fusion zone of single pass arc welding of structural steel (NST 34 L-C) (2008)
Some welded structures show poor mechanical properties at the weld and the adjacent zones. This has led to the collapse of structures when subjected to various torques. This research investigates the grain structure of the fusion zone of a single pass arc welding of structural steel to identify the mode of growth and grain transition of the zone and adjacent weld. Two parameters -temperature gradient in the direction of solidification and rate of advance of solidification were studied vis-a-vis welding speed, arc current and plate thickness. The results showed that chances in the welding variables affected the mechanical properties of the welded structure.